The Bible in the American short story - Stahlberg, Lesleigh Cushing; Hawkins, Peter S. (London : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc., 2018)
The Bible in the American Short Story examines Biblical influences in the post-World War II American short story. In a series of accessible chapters, Lesleigh Cushing Stahlberg and Peter S. Hawkins offer close-readings of short stories by leading contemporary writers such as Flannery O'Connor, Allegra Goodman, Tobias Wolff and Kirstin Valdez Quade that highlight the biblical passages that they reference. Exploring episodes from the Hebrew Bible and the New Testament and both Jewish and Christian heritages, this book is an important contribution to understanding the influence of the Bible in contemporary literature
America as a Biblical nation and the Bible as an American book -- The short story as an American genre -- The greatest stories ever told -- Flannery O'Connor -- Allegra Goodman -- John Updike -- Jamie Quatro -- Steven Millhauser -- Kirstin Valdez Quade -- Tobias Wolff -- Bernard Malamud -- Nathan Englander
Includes bibliographical references and indexes
Print version record
eBooks on EBSCOhost
Keywords: Bible -- In literature; Bible; Short stories, American -- History and criticism; American literature -- 20th century -- History and criticism; American literature -- 21st century -- History and criticism; Nouvelles américaines -- Histoire et critique; Littérature américaine -- 20e siècle -- Histoire et critique; Littérature américaine -- 21e siècle -- Histoire et critique; Literary studies: fiction, novelists & prose writers; Literary studies: from c 1900.; LITERARY CRITICISM -- American -- General; American literature; Literature; Short stories, American; 1900-2099; Criticism, interpretation, etc